How to predict the outcome of septorhinoplasty?: A normative study of ROE and FROI-17 scores = Prevedere l’esito della settorinoplastica? : valori di riferimento per i questionari ROE e FROI-17 - Plath, Michaela; Sand, Matthias; Cavaliere, Carlo; Plinkert, Peter K.; Baumann, Ingo; Plath, Karim (Acta otorhinolaryngologica italica, 2021)
Objective. Normative values of patient-reported outcome instruments are needed to iden- tify good candidates for rhinoplasty. Rhinoplasty Outcome Evaluation (ROE) and Func- tional Rhinoplasty Outcome Inventory-17 (FROI-17) are disease-specific questionnaires that evaluate quality of life in patients undergoing rhinoplasty.Methods. The reference cohort contained 1,000 participants, selected from a non-probabil- ity panel. Normative ROE and FROI-17 scores from this reference cohort were compared with ROE and FROI-17 scores from a patient cohort before (n = 104) and 6 (n = 55) and 12 months (n = 32) after septorhinoplasty.Results. Mean FROI-17 scores (± SD) were: overall score, 20.8 ± 17; nasal symptoms, 16.8 ± 7; general symptoms, 24.8 ± 22; and self-confidence, 16.4 ± 21. The ROE total score was 73.1 ± 16. Normative values differed significantly from the preoperative ROE and FROI-17 scores of septorhinoplasty patients (p < 0.01). Except for the FROI-17 gen- eral score at 12 months postoperatively (p = 0.004), there were no significant differences between normative ROE/FROI-17 and septorhinoplasty scores postoperatively, indicating that they returned to normalcy.Conclusions. Normative scores for ROE and FROI-17 provide a reference point from which to identify patients who are most likely to benefit from rhinoplasty.
Gesehen am 07.12.2021